Vice-Chancellor Awards goes to Rashwini - Nor Salwana, Mohammad Idris (2022)
PAYA BESAR, 5 November 2022 – Being active in co-curriculum and association at Universiti Malaysia Pahang (UMP) is not an excuse for being left behind in study.